Nutritional Wasting Disorders in Sheep - Javier Asín; Gustavo A. Ramírez; Mauricio A. Navarro; Akinyi C. Nyaoke; Eileen E. Henderson; Fábio S. Mendonça; Jéssica Molín; Francisco A. Uzal (Animals, 2021)
The different ovine production and breeding systems share the cornerstone of keeping a good body condition to ensure adequate productivity. Several infectious and parasitic disorders have detrimental effects on weight gains and may lead to emaciation. Flock health management procedures are aimed to prevent such conditions. Nutritional management is equally important to guarantee adequate body condition. Persistent bouts of low ruminal pH due to excess concentrate in the diet may lead to subacute ruminal acidosis. Pre-stomach motility disorders may also lead to ill-thrift and emaciation. An adequate mineral supplementation is key to prevent the effects of copper, selenium, and other micronutrients deprivation, which may include, among others, loss of condition. This review elaborates on the clinico-pathologic, diagnostic, and therapeutic aspects of some of these conditions, and highlights the necessity of considering them as contributors to states of wasting in sheep flocks.